The Institutionalisation of Bioculturalism through Community Protocols: The Case of Guna Yala - Foyer, Jean; Martinez Mauri, Monica; Filoche, Geoffroy; Castillo, Geodisio (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2024)
Biocultural Community Protocols (BCPs) are environmental governance mechanisms for biodiversity that aim to establish, at the local community level, a normative framework for the central themes discussed in the framework of the Convention on Biological Diversity (biodiversity conservation, traditional knowledge, prior and informed access, benefit sharing, agro-biodiversity conservation, etc.). Taking into account the Guna history about the idea of biocultural diversity, but also the specificities of the Guna political system, this article aims to shed light on the local implementation of this type of protocol in the indigenous territory of Guna Yala (Panama).We thus show that, despite the active role played by Gunas experts at the international, national, and regional levels, the Gunas have not adopted BCP's. Due to the pre-existence of research regulation mechanisms in GunaYala, but also to a certain mistrust of global environmental governance, the Guna authorities have for the time being not considered the BCP’s as being relevant enough. Beyond this particular example of unfinished institutionalization, BCPs must be understood as a localized mechanism serving the advancement of the more general idea of biocultural diversity.